Alternative Energy of Biomass Briquettes from Alaban Wood and Rubber Seed Shells with Rubber Sap Adhesive and Dyeing Used Cooking Oil - Ninis Hadi Haryanti; Nova Annisa; Suryajaya Suryajaya; Surini Surini (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
The increasing demand for energy and fossil fuels has caused a shortage of energy, so renewable alternative energy is needed to help solve this problem. Biomass waste has significant potential as a briquette-making material. The production of briquettes as an alternative energy source made from biomass from Alaban wood charcoal and rubber seed shells is one solution. The research was conducted to determine the characteristics of briquettes with differences in composition variations, including moisture content, ash content, and caloric value in accordance with SNI 01-6235-2000 standards. Alaban wood charcoal and rubber seed shells that have been carbonized and made into powder were then sieved with a 60 mesh sieve and then weighed and mixed with a rubber adhesive, and then molded with a pressure of 200 kg/cm2. The composition variations used for Alaban wood charcoal and rubber seed shells are 100%:0%; 0%:100%; 70%:30%; 60%:40%; 50%:50%; 40%:60%; 30%:70% with 9% rubber adhesive in the total weight for each composition and dipped in used cooking oil for 3 minutes. The characteristics of the resulting briquettes are moisture content of 0.69%-2.06%; ash content of 3.34%-4.91%; and caloric value of 7.863kcal/g-8.042kcal/g. The results of this research as a whole have met the standards. The more rubber seed shells that are added, the lower the moisture content, the higher the ash content, and the caloric value. Briquettes with a composition of 30% Alaban wood charcoal and 70% rubber seed shells produce a caloric value of 7.953 kcal/g, moisture content of 0.75%, and ash content of 4.19%.